1`-(п-ОКСИФЕНИЛ)ФЕРРОЦЕНКАРБОН КИСЛОТА СИНТЕЗИ (Scientific journal of the Fergana State University, 2023)
The article states aromatic derivatives and their significance, the synthesis of the new 1'- (p-hydroxyphenyl) ferrocenecarboxylic acid by the diazotization reaction of ferrocene p-aminophenol, as well as the study of its structure by IR spectroscopy.